Clinical outcomes of percutaneous coronary intervention in patients turned down for surgical revascularization. Issue 1 (21st September 2016) - Sukul, Devraj; Seth, Milan; Dixon, Simon R.; Zainea, Mark; Slocum, Nicklaus K.; Pielsticker, Elizabeth J.; Gurm, Hitinder S.
Abstract : Objectives: We examined clinical outcomes following percutaneous coronary intervention (PCI) in patients turned down for surgical revascularization across a broad population. Background: Prior studies suggest that surgical ineligibility is associated with increased mortality in patients with unprotected left main or multivessel coronary artery disease undergoing PCI. Methods: This study included consecutive patients who underwent PCI in a multicenter registry in Michigan from January 2010 to December 2014. Surgical ineligibility required documentation indicating that a cardiac surgeon deemed the patient ineligible for surgery. In‐hospital outcomes included mortality (primary outcome), cardiogenic shock, cerebrovascular accident, contrast‐induced nephropathy (CIN), and a new requirement for dialysis (NRD). Results: Of 99, 370 patients at 33 hospitals with on‐site surgical backup, 1, 922 (1.9%) were surgically ineligible. The rate of ineligibility did not vary by hospital (range: 1.5–2.5%; P  = 0.79). Overall, there were no major differences in baseline characteristics or outcomes between surgically ineligible patients and the rest (i.e., nonineligible patients): mortality (0.52% vs. 0.52%; P  > 0.5), cardiogenic shock (0.68% vs. 0.73%; P  > 0.5), cerebrovascular accident (0.05% vs. 0.19%; P  = 0.28), NRD (0.16% vs. 0.19%; P  > 0.5), CIN (2.7% vs. 2.3%; P  = 0.27). Among 1, 074 patients who underwent unprotected left main PCI, 20 (1.9%) were surgically ineligible and experienced increased rates of mortality (20.0% vs. 5.3%; P  = 0.022; adjusted OR = 7.38; P  < 0.001) and other complications as compared to the remainder. Conclusions: PCI in a broad population of surgically ineligible patients is generally safe. However, among patients who underwent unprotected left main PCI, those deemed surgically ineligible experienced significantly worse outcomes as compared to the rest. © 2016 Wiley Periodicals, Inc.